Like Plato’s ‘two worlds’: LSP practitioners’ roles between the academia and the profession - Muñoz, Verónica Lilian; Fuenzalida Caspar, Gisella; Galfioni, Gabriela; Roccia, Valentina (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This reflective article aims to contribute to the analysis of the roles of practitioners of languages for specific purposes. We analyse and evaluate theoretical discussions on the roles of practitioners in the field of English for specific purposes (ESP). This issue, of academic and pragmatic concern, should be re-oriented considering fundamental theoretical underpinnings that can better equip scholars to discuss ESP practitioners’ roles. For a better understanding of these roles, it is essential to consider the dual identity of the ESP field, lying between the academia and the profession. ESP practitioners are dwellers of two territories, like Plato’s ‘two worlds’: the abstract or intelligible world of academic disciplines, and the material or sensible world of professional jurisdictions. Then, we argue that it is necessary to discuss ESP practitioners’ roles contextualising them to their real settings, a contextualisation which would be misleading if this dual identity were not considered.